Comitês de investimento em fundos de investimento em participações utilizados como veículos para a indústria de Private Equity - Barros, Guilherme Smolarek de (2012)
This paper investigates whether or not the existence of advisory committees that grant quota holders interference in the decision making process is considered by potential investors of Brazilian Fundos de Investimento em Participações which are used as vehicles for Private Equity investments ('Brazilian PE Fund') a relevant corporate governance mechanism, able to interfere in such investors choice of which Brazilian PE Fund they are going to invest. Its objective is to verify whether or not managers of Brazilian PE Funds compete for including such advisory committees in the structure of the funds they raise, aiming to gather a larger number of investors. In order to fulfill such objective, a research under which will be analyzed the documentation concerning all Brazilian PE Funds registered before the Brazilian securities commission (Comissão de Valores Mobiliários) between 2006 and 2011 will be made, searching for empirical evidence that in fact the existence of advisory committees that grant quota holders interference in the decision making process is relevant for potential investors of Brazilian PE Funds and, therefore, that managers of Brazilian PE Funds compete for including such advisory committees in the structure of the funds they raise. This work also presents the theoretical concepts that justify the adoption of corporate governance mechanisms by Brazilian PE Funds, specially focusing on the literature concerning the agency theory, with emphasis to the themes of informational asymmetry, adverse selection, economic costs of dishonesty and agency costs, as well as the corporate governance mechanisms more commonly used in the Brazilian Private Equity industry. The relevance of this work derives from the importance of the Private Equity industry in the Brazilian economy, thus such investments are usually made in a development stage where the companies are not able to find proper funding, thought debt or equity. Besides, the subject herein shows itself up to date, considering that in 2011 it was registered the largest Private Equity fundraising in Brazil, in an amount of US$ 8.1 billion.